Analysis of trace metal concentration in a degraded lagoon in East Otago, New Zealand - MJ Desmond; RJ McLeod; CD Hepburn (New Zealand Journal of Marine and Freshwater Research, 2013)
The decline in ecological health of coastal lagoon systems over the last 150 years is globally recognised. The aim of this study was to determine if sediment metal contamination may be a factor contributing to the current degraded state of Mataīnaka Lagoon. The concentration of 44 metals were analysed from the sediment of Mataīnaka, the main inflow to the lagoon (Post Office Creek) and two analogous sites considered less impacted, the Waikouaiti River and Stony Creek Lagoon. In‐depth analysis was conducted specifically on As, Cd, Cr, Cu, Mn, Ni, Pb, Sn and Zn which have all been demonstrated to have toxic effects in the aquatic environment. Localised Cd contamination, −1 , was present within the surface sediment of Mataīnaka. A multidimensional scaling (MDS) ‘fingerprint’ of surface sediment was constructed using an array of 23 metals from all four sites. The metal fingerprint of Mataīnaka was not statistically distinct from the other three sites. Sediment metal concentrations within Mataīnaka were found to be most similar to sites considered uncontaminated in the literature, with the exception of Cd. The degraded state of Mataīnaka is unlikely to be a result of sediment metal contamination as most metals were present within the sediment at concentrations below the threshold effect level for aquatic organisms.